2007
DOI: 10.1371/journal.pmed.0040115
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Infection: Complex Mechanisms and Global Impacts

Abstract: The authors discuss current concepts and controversies surrounding the complex influences of malnutrition on infection and immunity, and point to practical consequences of countermeasures in acute malnutrition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
604
2
27

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 751 publications
(645 citation statements)
references
References 70 publications
(76 reference statements)
12
604
2
27
Order By: Relevance
“…HIV can also impair lymphocyte functions against malaria infection [61]. Similarly, malnutrition can lead to atrophy of the thymus, leucopenia, and diminished functional T cells that hamper protective immunity to malaria [62]. …”
mentioning
confidence: 99%
“…HIV can also impair lymphocyte functions against malaria infection [61]. Similarly, malnutrition can lead to atrophy of the thymus, leucopenia, and diminished functional T cells that hamper protective immunity to malaria [62]. …”
mentioning
confidence: 99%
“…8,10,16,17 In both incidence and the rate of development into more serious infections, a relation has also been established between upper respiratory tract infections and malnutrition. 7,9,18 For the specific factor of growth rate, some studies have shown a relationship between growth faltering and gastroenteritis. [11][12][13] A combined analysis of data from nine studies in five countries (Bangladesh, Brazil, Ghana, Guinea-Bissau and Peru) shows that 25% of stunting at 24 months of age was associated with five or more episodes of gastroeneteritis in the first 2 years of life.…”
Section: Relationship Between Weight Gain and Infectionmentioning
confidence: 99%
“…1,2 When an infection happens, the immune system needs various nutrients to maintain immunity against pathogens. Various hypothesis has said that frequent infections may make nutritional interventions may not as effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The association between TB and DM occur in low-and medium-income countries, where roughly 95% of patients with TB and 70% of patients with DM live. 8 Patients with DM are at twice the risk of acquiring TB compared to those without DM, and that this association is even stronger in HIV positive subjects. 9 Moreover, DM patients with smearpositive pulmonary TB have a higher probability of failure of the sputum smear conversion after 2 months of therapy than patients without DM.…”
mentioning
confidence: 96%